2009
DOI: 10.1177/1524839909334621
|View full text |Cite
|
Sign up to set email alerts
|

Using Action Research to Implement an Integrated Pediatric Asthma Case Management and eHealth Intervention for Low-Income Families

Abstract: Asthma case management and education programs improve pediatric asthma outcomes, but designing rigorous randomized controlled studies that accurately measure effects while encouraging parent participation is challenging. This is especially so for low-income African American families, who face significantly more severe asthma and social stress than their middle-class counterparts. Action research can help health education researchers negotiate between the elegant and complex designs favored by scientists with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The Internet Telehealth for Pediatric Asthma Case Management intervention (Wise et al, 2007) offers online opportunities for parents to post messages on bulletin boards as well as monthly professional support for parents via telephone. However, the protocol has been difficult to implement because it is staff-intensive and time consuming (Wise et al, 2010).…”
mentioning
confidence: 99%
“…The Internet Telehealth for Pediatric Asthma Case Management intervention (Wise et al, 2007) offers online opportunities for parents to post messages on bulletin boards as well as monthly professional support for parents via telephone. However, the protocol has been difficult to implement because it is staff-intensive and time consuming (Wise et al, 2010).…”
mentioning
confidence: 99%
“…Patient-centered care was another strength of CM. In the studies reviewed, CM interventions provided patient- or participant-centered care because NCMs could assess needs and deliver care plans based on those needs (Brennan-Ing et al, 2016; Kneipp et al, 2011; Wise et al, 2011). These and other researchers reported that NCMs’ activities were uniquely suited to effective care transitions, which resulted in continuity of care (Baldwin et al, 2014; Gary et al, 2009; Joo, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, research into how CM might be affected by technological development is recommended. One study accessed electronic health records to check patients’ discharge information and record intervention dosage (Baldwin et al, 2014), and other studies used telephonic or online-based education (Kahn et al, 2009; Wise et al, 2011). Applying technologies such as these is one way to make CM more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…The study team traveled twice a month to the community center to conduct intakes after school and into the early evening [40]. At all locations, childcare, snacks, and transportation were provided as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Randomization occurred upon receipt of the run in diaries for MCO 1-4 subject and after just the intake for MCO 5 participants [40]. The CHESS+CM group received a 45-minute training session.…”
Section: Methodsmentioning
confidence: 99%